Do evento ao fato: o realismo peirceano como intersecção entre o real, o signo e o direito - Passos, Raphael Ricardo de Faro (2017)
The present study refers to event and/or fact as the phenomenological basis for an intersection between reality, sign and the law. The study arises firmly grounded on Peirce’s realism alongside introspections on diverse schools of realism, passing through antiquity, the Middle Ages, modern and contemporary periods. The philosophical model is instigated, equally, by the ideas of Merleau-Ponty and Lacan, principally in reference to the gaze that is the interrelationship between man and nature. From there emerges a symbiotic relationship between the sign and the sensitive world in a shuffling of layers relating to Peirce’s ceno-pythagorean categories of firstness, secondness, thirdness. As such, the philosophical parameter appears in order to show that, in terms of sign, there is a sort of imprinting phenomenon of the object onto the subject, deriving from it, an imprinting process that goes on ad infinitum from one sign to the other. That entails two types of signs: imprinting signs and imprinted signs and also two sorts of reality: semeiotic reality (reality of the sign) and summa reality (reality where the events are). The philosophical model is then applied to the law seen as language – a collection of signs (legal signs), which are viewed as imprinting legal signs over the imprinted signs of the ordinary language. In such a context, as the conclusion is that ordinary language extends to the object of summa reality as a result of a continuum of investigation in the sensitive experience, which will be the foundation that will allow legal communication between those who are subject to the law, the findings were that a more adequate theory to describe the legal phenomenon is a so-called “semeiotical↔esthesiological legal theory”. As a reslt of it, the work’s hypothesis is that the law is an esthesiological-semeiotical phenomenon, from which signs tend, in a continuum, to be interrelated to the summa reality, allowing legal communication to be efficiant and, ultimately, the survival of the law in a symbiotic manner to be seen as a social ingredient